A "win–win" nanoplatform: TiO2:Yb, Ho, F for NIR light-induced synergistic therapy and imaging. Issue 12 (14th March 2017) - Zhou, Jie; Luo, Pei; Sun, Chong; Meng, Lingchang; Ye, Weiran; Chen, Shanshan; Du, Bin
Abstract : To avoid the defect of low energy transfer efficiency in core–shell UCNP-TiO2 NPs, doping rare earth into TiO2 and improving the photocatalytic activity of TiO2 itself under Vis-NIR light might be a more direct and efficient strategy for high 1 O2 production. Abstract : To avoid the defect of low energy transfer efficiency in core–shell UCNP-TiO2 NPs, doping rare earth into TiO2 and improving the photocatalytic activity of TiO2 itself under Vis-NIR light might be a more direct and efficient strategy for high 1 O2 production. Here, we designed a TiO2 :Yb, Ho, F-β-CD@DTX/HA nanoplatform using TiO2 :Yb, Ho, F as the core, β-CD as the drug carrier, hyaluronic acid (HA) as the capping agent and target, and then applied it for 808 nm induced photodynamic-chemotherapy and 980 nm upconversion fluorescence/MR imaging. The results were as follows: (i) for TiO2 as a photosensitizer, after doping Yb, Ho, F into TiO2, it could directly generate reactive oxygen species under an 808 nm laser; the dopants enhanced the absorption under the UV-Vis-NIR region and increased the electron–hole pair separation. (ii) For TiO2 as the upconversion host, F and Ho also endowed TiO2 :Yb, Ho, F with enhanced upconversion fluorescence under a 980 nm laser and T 2 -MRI contrast performance ( r 2 = 30.71 mM −1 s −1 ), respectively, thus, facilitating imaging for deep tissues. (iii) The HA shell outside of β-CD prevented the unexpected leaking of DTX, which improved the target abilities and achieved the enzyme-responsive drug release. The in vitro and in vivo studies also demonstrated the nanosystem could efficiently suppress tumor growth by combination therapy and had excellent imaging (UCL/MR) ability. Particularly, our work was the first example that utilized TiO2 simultaneously as a photosensitizer and upconversion host, which simplified the core–shell UCNP-TiO2 nanocomposites and reached a "win–win" cooperation in NIR-induced photodynamic therapy and UCL imaging.